Analyzing the Determinants of Child Nutrition in Rural Bangladesh: Application of Quantile Regression - Hossain, Mahbub; Mandal, M A Sattar (Bangladesh Journal of Nutrition, 2021)
Despite recent success in achieving major development goals, Bangladesh still lags behind in respect of reducing the incidence of child undernutrition which usually causes illness, poor physical and cognitive development, or even death. Recognizing the importance of child nutrition stated in the Sustainable Development Goals, the Government of Bangladesh is keen on making success in reducing child malnutrition in the country, especially in the rural areas. In this respect, it is imperative to understand what determines child nutrition and whether or not the child nutrition determining factors exert similar effects at different points of the distribution of child nutrition. By using data from three rounds of a nationally representative rural household survey, this paper finds that child’s gender, age, and birth weight, parents’ education and their health, household’s socioeconomic status, and availability of local health care facility are crucial in determining child nutrition. Furthermore, quantile regression results suggest that the effects of these determinants tend to vary across different points of the nutritional status. Nonetheless, parents’ health and birth weight seem to have strong influence which is consistent throughout the distribution of child nutritional status. Thus, the findings of this paper have policy relevance, which is worthy of the attention of the national and international development partners in Bangladesh. Bangladesh J. Nutr. Vol. 34, December 2020, P: 15-24